2014
DOI: 10.5897/jmpr2013.5036
|View full text |Cite
|
Sign up to set email alerts
|

Amazing bean Mucuna pruriens: A comprehensive review

Abstract: Mucuna pruriens commonly known as cow-age or cowitch or velvet bean or Alkushi, is a medicinal plant traditionally used in Indian medicine belongs to the family Leguminosae. M. pruriens seed is a natural source of the amino acid L-3,4-dihydroxy phenyl alanine (L-DOPA), the direct precursor to the neuro transmitter dopamine which is used widely in the treatment of Parkinson's disease (PD). Serotonin, oxitriptan, nicotine, N,N-DMT, and bufotenine are the other chemicals found in M. pruriens in addition to L-DOPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…The only seed found to have enough L‐Dopa for possible commercial use belongs to the genus Mucuna (Leguminosae) . Mucuna pruriens , a tropical legume of the family Fabaceae has a nutritional quality comparable to that of soybeans and other conventional legumes, since it contains similar proportions of proteins, lipids, minerals, and other nutrients . This plant has a high enough content in L ‐ Dopa to warrant possible commercial production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only seed found to have enough L‐Dopa for possible commercial use belongs to the genus Mucuna (Leguminosae) . Mucuna pruriens , a tropical legume of the family Fabaceae has a nutritional quality comparable to that of soybeans and other conventional legumes, since it contains similar proportions of proteins, lipids, minerals, and other nutrients . This plant has a high enough content in L ‐ Dopa to warrant possible commercial production.…”
Section: Introductionmentioning
confidence: 99%
“…Mucuna pruriens, a tropical legume of the family Fabaceae has a nutritional quality comparable to that of soybeans and other conventional legumes, since it contains similar proportions of proteins, lipids, minerals, and other nutrients. 2,3 This plant has a high enough content in L-Dopa to warrant possible commercial production. In fact, M. pruriens is among the plants used in Ayurveda, India's ancient medical system to fight disease, including Parkinson's.…”
mentioning
confidence: 99%
“…Believed to have relatively lower negative side effects, herbal is more preferable than synthetic medicine [16][17][18]. L-Dopa is an important component of velvet beans [22]. As previously studied, L-dopa and other substances found in velvet beans have been proven effective in improving the sexual performance of albino male mice [23].…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, this plant is also used in the treatment of cholesterol, diabetes, hypertension, paralysis, rheumatism, cancer, tumors, tuberculosis, asthma, cholera, diarrhea, dysentery, irritation, burns, cough, muscle pain, and many others [5][6][7]. Various studies reported the bioactivity of Mucuna pruriens, such as increasing the sexual activity of normal male rats, hepatoprotective activity with increasing the in vivo antioxidants [8], antidiabetic activity [9][10][11][12], and as a potential antiparkinson from the seeds [13,14].…”
Section: Introductionmentioning
confidence: 99%